Desiccation time of the spring sorghum as a predecessor crop for summer soybean and autumn bean in a no-tillage system - Denadai, Marcelo S. [UNESP]; De Mello, Luiz M.M. [UNESP]; Chioderoli, Carlos A.; De Niro Gazola, Rodolfo [UNESP] (FapUNIFESP (SciELO), 2016)
Several authors have been questioned the desiccation interval between the coverage plants and sowing plants for the soybean crop. Therefore, this study aimed to evaluate the desiccation time of the spring sorghum as a predecessor crop for summer soybean and then for autumn bean, focusing on the straw formation for maintenance of the no-tillage system and to evaluate the yield of soybeans and beans grain, as well as analyzing the interference of sorghum straw in these cultures. The experiment was developed in the Teaching and Research Farm of FE/UNESP located in Ilha Solteira/SP where it was used an experimental design of randomized blocks with five treatments and six repetitions. The treatments consisted of five different intervals between sorghum desiccation and soybean sowing (being with D7 - Drying sorghum seven days before the soybean sowing; and successively for D14, D21, D28 and D35). In order to analyze the results, it was used the Tukey test for a 10% level of significance and the statistical program called Sisvar. The Cober Crop sorghum exerted influence on soybean yield but this effect was not lasting for the bean crop in succession to the soybeans.
Keywords: Crop rotation; Desiccation interval for sowing; Exudates allelochemicals; Soil cover; Straw production